MATHEMATICAL MODEL OF PHYSICAL PROPERTIES CHANGE OF COCONUT SAP IN THE VACUUM EVAPORATOR - Febryan Kusuma Wisnu; Sri Rahayoe; Rizza Wijaya; Mareli Telaumbanua; Agus Haryanto (Jurnal Teknik Pertanian Lampung (Journal of Agricultural Engineering), 2021)
The potential of brown sugar as a substitute for granulated sugar is enormous considering the abundant coconut sap production. However, the quantity of brown sugar production through the traditional method is one of the main obstacles. This study used a vacuum evaporator that emphasizes the hygienic and effective mass production of brown sugar. For this reason, it is necessary to approach changes in the physical properties of sap juice during the cooking process. This knowledge is indispensable in the cooking process, which involves the proper evaporation and crystallization of brown sugar. This research is devoted to determining the viscosity, density, and dissolved solids expressed in Brix and proposes a mathematical model to predict the physical properties during the evaporation process of brown sugar as a function of the initial concentration the solution before proceeding to the crystallization process. Results confirm that the prediction model for Brix is Cθ=(Co–Ce)·exp(0.0067·t)+Ce, the model for viscosity µθ=µo·exp(0.011·t), and ρө=(0.44996·t)+ρ0 for the density prediction model. The resulted mathematical model can accurately predict the rate of change in coconut sap's physical properties, indicated by the high coefficient of determination (R2). Keywords : brix, brown sugar, density, vacuum evaporator, viscosity